Artificial Intelligence in Education - Noura Saleh Al-Bahijan,; Hessa Abdullah Al-Suraibi,; Joud Hajeel Al-Otaibi,; Kholoud Obaid Al-Otaibi, (International Journal of Computers and Informatics, 2025)
This research paper was titled: (Artificial Intelligence in Education), and through it, the researchers sought to explore the main role that artificial intelligence represents as a modern and advanced technical achievement in the fields of education and learning at its various stages. The paper was divided into six sections, the first of which represents the methodological framework of the research, the second on the concept of artificial intelligence in education and its importance, the third included applications of artificial intelligence in education, the fourth shed light on the use of artificial intelligence in education and the challenges, controls, effects and ethical concerns that accompany it, the fifth was devoted to future trends in artificial intelligence in education in the Kingdom, and the sixth contained the results, recommendations and references. The researchers concluded with a number of results, the most prominent of which are: the importance of combining artificial intelligence and teachers to achieve the best educational results, the positive impact that artificial intelligence-supported tools achieve in improving the quality of education, and the role of artificial intelligence in reducing routine burdens on teachers and enabling them to focus on aspects of creative teaching.
Keywords: Artificial Intelligence; Artificial Intelligence in Education; Quality of Education; Creative Teaching